LEGAL AND MORAL AND ETHICAL PROBLEMS OF TRANSPLANTATION IN UKRAINE - Palchenkova, Viktoriia M.; Olena, Riabchynska; Olena, Gorokhovska; Eduard, Stomatov; Myrnyi, Sergii P. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article analyzes the legal acts, modern scientific approaches to the implementation of transplantation as an alternative method of treatment of many diseases, as well as the state policy in this area, identifies the main legal and moral and ethical problems of transplantation in Ukraine, and makes recommendations for improving the state policy in the field of transplantation in order to solve them.